2013
DOI: 10.1536/ihj.54.222
|View full text |Cite
|
Sign up to set email alerts
|

Everolimus-Incorporated Immunosuppressant Strategy Improves Renal Dysfunction While Maintaining Low Rejection Rates After Heart Transplantation in Japanese Patients

Abstract: SummaryThe long-term survival of heart transplantation (HTx) recipients has increased significantly in recent years, however, the nephrotoxic adverse effects of calcineurin inhibitors (CNIs) are still a major concern. Recently, an inhibitor of mammalian target of rapamycin, everolimus (EVL), has emerged as an alternative immunosuppressant drug that may allow CNI dosage reduction and thereby spare renal function. Data were collected from 20 HTx recipients who had received EVL (target trough level 3-8 ng/mL) alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 37 publications
1
11
0
Order By: Relevance
“…13) CNI-minimization or free regimens plus EVL have advantages in terms of the improvement of renal function among heart or renal transplantation recipients, and EVL-incorporated regimens have recently been increasing. [16][17][18][19][20] Recent clinical studies including ours also demonstrated the suppressive effects of EVL in cardiac allograft vasculopathy and post-transplant malignancy. [21][22][23][24][25] Considering that both SRL and EVL are mTOR inhibitors, EVL may also have a repressive effect on LVM.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-supporting
confidence: 61%
See 1 more Smart Citation
“…13) CNI-minimization or free regimens plus EVL have advantages in terms of the improvement of renal function among heart or renal transplantation recipients, and EVL-incorporated regimens have recently been increasing. [16][17][18][19][20] Recent clinical studies including ours also demonstrated the suppressive effects of EVL in cardiac allograft vasculopathy and post-transplant malignancy. [21][22][23][24][25] Considering that both SRL and EVL are mTOR inhibitors, EVL may also have a repressive effect on LVM.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-supporting
confidence: 61%
“…[13][14][15] However, little is known about how the next generation mTOR inhibitor derivative everolimus (EVL) affects LVM. 13,16,17) EVL has become thus far a major mTOR inhibitor for immunosuppression therapy because of its superiority in terms of fewer adverse effects compared to SRL. 13) CNI-minimization or free regimens plus EVL have advantages in terms of the improvement of renal function among heart or renal transplantation recipients, and EVL-incorporated regimens have recently been increasing.…”
Section: Eft Ventricular Hypertrophy (Lvh) Is Observed In Pa-mentioning
confidence: 99%
“…The new immunosuppressant EVL, which is a mammalian target of rapamycin, has recently been demonstrated to have various advantages in terms of its prophylactic effect of CMV infection, 8,13) suppressive effect of cardiac allograft vasculopathy, [14][15][16] anti-malignancy effect, 17,18) and maintenance of renal function, 19) and subsequently its use has increased around the world. Although EVL has been reported to have a prophylactic effect towards PTLD, 18) it may not necessarily protect the development of early-PTLD completely considering the findings in the present patient.…”
Section: Discussionmentioning
confidence: 99%
“…10) Immunosuppression regimen consisted of cyclosporine, or tacrolimus, mycophenolate mophetil, and/or everolimus with low dose prednisolone as described in our previous study. 7,11) All patients had sinus rhythm, and anyone with arrhythmias or mechanical pacing was excluded. All patients gave informed consent before their enrollment in the study.…”
Section: Methodsmentioning
confidence: 99%